Users of open Big Earth data – An analysis of the current state. (December 2021) - Wagemann, Julia; Siemen, Stephan; Seeger, Bernhard; Bendix, Jörg
Abstract: The broad dissemination of open data policies for Big Earth data leads to a diversification of users. The literacy in data and data handling differs for each user group, resulting in different needs and requirements. In addition, the development of cloud-based data systems challenges traditional workflows of all users. In order to tailor new cloud-based data systems for Earth data users, it is of utmost importance to obtain a better understanding of users in terms of the type of data they explore, the applications they need the data for, the way they access and process data, and the challenges they face. This is an indispensable prerequisite to ensure an increased uptake of Big Earth data in the future. In order to get a better insight in the requirements and challenges of users coping with Big Earth data, we run a comprehensive web-based user survey. Our results, inclined to users of Big Earth data in Europe and the North American continent, reveal that a majority of survey respondents still download copies of data onto their local machine and handle and process data locally with a combination of programming and desktop-based software. However, survey respondents are facing severe problems related to the growing data volumes, the data heterogeneity and the limited processing capacities for their demanding applications. Thus, they show a specific interest in using cloud-based data services in the near future but express the need for an easier data discovery and the interoperability of data systems. Based on the survey findings, we draw a set of recommendations to make Big Earth data more FAIR (findable, accessible, interoperable and re-useable). Highlights: User requirements are a driving force of the development of emerging cloud-based systems for Big Earth data. Growing data volume and limited processing capacity top Big Earth data challenges. Cloud-based data systems are not broadly used but attract user's interest and are preferred over 'user-centric' platforms. The formation of a global cloud consortium can help to make the Big Earth data landscape more FAIR in the future.